Optimizing screening, brief intervention, and referral to treatment (SBIRT) training for nurses and social workers: Testing the added effect of online patient simulation. Issue 4 (2nd October 2019) - O'Brien, Kimberly H. McManama; Putney, Jennifer M.; Collin, Cali-Ryan R.; Halmo, Rebekah S.; Cadet, Tamara J.
Abstract: Background: Social workers and nurses are critical to the amelioration of substance misuse, making their training in evidence-based practices such as screening, brief intervention, and referral to treatment (SBIRT) particularly pertinent. Online patient simulation (OPS) is one training modality that allows students to develop and practice SBIRT skills that they might not obtain through didactic instruction, but it can be time and resource intensive. The aim of this study was to test the effect of OPS, over and above in-person training, on students' SBIRT attitudes, knowledge, and perceived skills. Methods: Social work and nursing students ( N = 308) were recruited from a college in the northeastern United States. Students in the study were randomly assigned to either training as usual (TAU), which included pre-coursework videos, in-person didactic instruction, and role-plays, or the experimental condition (EXP), consisting of TAU plus access to self-paced SBIRT skills practice using OPS by SIMmersion. The SBIRT Attitudes, Self-perception of Skills, and Knowledge (AKS) survey was delivered at baseline, immediately post-training, and at 30-day follow-up (post-30) to assess overall changes as well as changes in the specific domains of SBIRT confidence, importance, and attitudes. Paired t tests were conducted to determine differences in mean scores between time points for the entire sample. Independent-samples t tests were conducted to test differences between EXP and TAU on AKS scores at each time point and to test differences between high and low OPS use. Results: Results showed a significant difference from pre- to post-training on composite AKS scores. There were no significant differences between TAU and EXP in composite scores or by AKS domain, and no differences within the EXP group for those with high and low use. Conclusions: Participants in EXP did not have significantly increased AKS scores, demonstrating that access to OPS did not produce an additive effect on the acquisition of self-perceived SBIRT knowledge, attitudes, and skills.